Short-term Effects of Diet and Activity Changes on Inflammation and Insulin Resistance - Desgorces, F.-D; Breuillard, C.; Police, C.; Neveux, N.; Cottart, C.-H; Blanc, M.-C.; Toussaint, J. F.; Noirez, P. (International Journal of Sports Medicine, 2016)
The present study focused on rapid responses of inflammation markers and insulin resistance to dietary restriction and exercise in inactive patients. 13 obese women were included during a 5-day time frame during which decreases in food intake (−1 378±298 kcal) were associated with 2 exercise sessions (80 and 40 min). Circulating inflammatory biomarkers, insulin resistance index and muscle soreness were measured in fasted conditions. Fasting plasma concentrations of CRP and insulin resistance index decreased over the period (respectively, p=0.02 and p=0.01), concentrations of IL-6 and TNF-α appeared unchanged (p>0.05). Changes in IL-6 (enhanced) and TNF-α (reduced) concentrations following the prolonged exercise differed compared to days with 40 min exercise and days without exercise (p<0.05). Muscle soreness appeared higher after the 80 min than after the 40-min exercise (p=0.01), and were related with IL-6 and CRP concentration changes. A 5-day period combining exercise and diet reduced the insulin-resistance index and the CRP fasting concentrations. The 80-min exercise enhanced IL-6 and lowered TNF-α concentration changes while days without exercise unaffected these cytokines. These exercise effects on cytokines may have benefited to the insulin resistance index. The duration and number of the exercise sessions appeared sufficient for inactive subjects to initiate health benefits without inducing negative effects on inflammation and muscle soreness.
Keywords: obesity; physical exercise; caloric restriction; interleukin-6; TNF-alpha